2016
DOI: 10.1105/tpc.15.01053
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Visualization of the Tubular-Lamellar Transformation of the Internal Plastid Membrane Network during Runner Bean Chloroplast Biogenesis

Abstract: Chloroplast biogenesis is a complex process that is integrated with plant development, leading to fully differentiated and functionally mature plastids. In this work, we used electron tomography and confocal microscopy to reconstruct the process of structural membrane transformation during the etioplast-to-chloroplast transition in runner bean (Phaseolus coccineus). During chloroplast development, the regular tubular network of paracrystalline prolamellar bodies (PLBs) and the flattened porous membranes of pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
75
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(85 citation statements)
references
References 95 publications
8
75
0
2
Order By: Relevance
“…From a functional viewpoint, the transition from the bicontinuous prolamellar body to the lamellar stacking is interesting, as it is triggered by light and is accompanied by the emergence and incorporation of the multisubunit, rigid membrane protein complexes responsible for photosynthesis. However, this light–matter interaction is not a photonic crystal effect due to the geometric structure of the prolamellar body; the length scale of the structure is substantially too small (e.g., 78 nm for the maize PLB) to create a photonic effect in the biologically relevant spectrum of light; similarly, the spacing of the grana lamellar stacking is of the order of a typical bilayer width and hence also much too small to cause photonic crystal effects; note that in some related iridoplast systems a spacing compatible with optical effects is generated through multilayer stacks . The purpose of the complex structural shape remains unknown, however it has been observed that stacked thylakoid membranes increase photosynthetic efficiency .…”
Section: Lipidic Lyotropic Liquid Crystalline Phases In Naturementioning
confidence: 99%
See 1 more Smart Citation
“…From a functional viewpoint, the transition from the bicontinuous prolamellar body to the lamellar stacking is interesting, as it is triggered by light and is accompanied by the emergence and incorporation of the multisubunit, rigid membrane protein complexes responsible for photosynthesis. However, this light–matter interaction is not a photonic crystal effect due to the geometric structure of the prolamellar body; the length scale of the structure is substantially too small (e.g., 78 nm for the maize PLB) to create a photonic effect in the biologically relevant spectrum of light; similarly, the spacing of the grana lamellar stacking is of the order of a typical bilayer width and hence also much too small to cause photonic crystal effects; note that in some related iridoplast systems a spacing compatible with optical effects is generated through multilayer stacks . The purpose of the complex structural shape remains unknown, however it has been observed that stacked thylakoid membranes increase photosynthetic efficiency .…”
Section: Lipidic Lyotropic Liquid Crystalline Phases In Naturementioning
confidence: 99%
“…All data to date stem from post vivo imaging, in stained and fixed tissue, or freeze‐fracture microscopy. With ever improving microscopy methods for living tissue and intracellular membrane organelle organization, both in vivo and post vivo (e.g., for the endoplasmic reticulum and for the prolamellar body in plants), we are likely to soon see a surge in structural data for biological nanostructured phases that will allow us to fully realize just how important they are in nature's building blocks of the nanoorganization of living materials. Since Dubochet et al invented the cryo‐TEM technique about 35 years ago, it has evolved substantially and recently enabled greater insight into artificially made lyotropic liquid crystalline phases using also tomography, averaging techniques to obtain 3D reconstruction and increase resolution .…”
Section: Lipidic Lyotropic Liquid Crystalline Phases In Naturementioning
confidence: 99%
“…Chloroplast biogenesis is a complex process and is highly integrated with cellular and plant development (Yang et al, 2010;Pogson et al, 2015). Although three-dimensional (3D) models of the thylakoid membrane architecture have been created using electron tomography of higher plant chloroplasts (Shimoni et al, 2005;Daum et al, 2010;Austin and Staehelin, 2011;Kowalewska et al, 2016) and Chlamydomonas reinhardtii chloroplasts (Engel et al, 2015), a 3D visualization of chloroplast changes in response to external stresses (e.g. viral attack) has not been investigated.…”
mentioning
confidence: 99%
“…Conditions that limit light, such as being covered by soil or litter (Solymosi and Aronsson 2013), also result in the formation of etioplasts. However, etioplasts transform into chloroplasts after short-term exposure to light (Kowalewska et al 2016).…”
Section: Introductionmentioning
confidence: 99%